(3GdahR GdCUZQ aj GdMceIs - (3CMeO Hf eMeO Hf jYbhH perSncnhrjg, CHh Ydj,J (B421 (3g` s ((3eMeO Hf MeOhf GdCUHgGfi s)
(3ChdgG (B:s
(3GHh Ydi CMeO Hf eSchjg GdcdGe Ydi GdeSGFd GdKdK GdJi jTJed Ydi GdYdhe s
(3BNQgG (B:s
(3hTQM Edi CeGcf ef cJGH GdYOO GdCcHQ GdPi jSJCfa s
(3NGdj ef GdfbWs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B168s
Keywords: (3GdadSaI hGdefWbs